Inhibition of catechol-O-methyltransferase activity by two novel disubstituted catechols in the rat - Nissinen, E; Lindén, I B; Schultz, E; Kaakkola, S; Männistö, P T; Pohto, P (European journal of pharmacology, 1988)
Catechol-O-methyltransferase (COMT) has an important role in the extraneuronal inactivation of catecholamine neurotransmitters and drugs with a catechol structure. Two novel COMT inhibitors, OR-462 and OR-486, were highly effective (IC50 = 18 and 12 nM, respectively) and selective in inhibiting COMT activity in vitro. Tyrosine hydroxylase was not inhibited until micromolar concentrations of these compounds were used: the IC50 values for OR-462 and OR-486 were 10 and 14 microM, respectively. The IC50 values for dopamine-beta-hydroxylase, dopa-decarboxylase and monoamine oxidase forms A and B were greater than 50 microM. In studies ex vivo oral OR-462 inhibited mainly the COMT activity in the duodenum while OR-486 inhibited COMT activity in the liver and red blood cells as well. Oral OR-462 did not penetrate into the brain in doses up to 30 mg/kg while the same dose of OR-486 had some effect on striatal COMT activity. When tested in combination with levodopa-carbidopa, orally administered OR-462 and OR-486 were more effective in reducing the formation of 3-O-methyldopa from levodopa than was the levodopa-carbidopa treatment alone. These results indicate that OR-462 and OR-486 are effective and long-lasting inhibitors of COMT activity.